The Effect of Employee Costs of Production, Marketing, and Salary On The Results of Broiler Chicken Sales - Baiza, Ahmad (International Journal of Social Service and Research, 2021)
"Rahmat Aulia" farm is part of PT Charoen Pokphand Jaya Farm. This farm is located in Kutatrieng Village, Labuhanhaji District, West Aceh. It has used good management in financing including production costs, marketing costs, and employee salaries. employee. The selection of research on the "Rahmat Aulia" farm due to the high level of sales competition in the broiler business (Gallus domestic) with this research is expected to be a reference for beginners and other breeders in facing competition. The type of research used is qualitative (interview). Where data collection uses interviews with related parties at the "Rahmat Aulia" farm as resource persons, and the sample used is the financial report of the "Rahmat Aulia" farm which has been recorded at PT Charoen Pokphand Jaya Farm in 2021 (3 months). The results of the study stated that 80% of sales results were strongly influenced by production costs, marketing costs, and employee salaries. While the remaining 20% ??of sales are influenced by other factors not explained in this study. From the results of the analysis, it is known that production costs, marketing, and employee salaries play a very important role in the sustainability of "Rahmat Aulia" farming in Kutatrieng Village, West Labuhanhaji District, South Aceh Regency.